Political stratification and democracy - Budge,Ian......[et al] (London, 1972)
Most of the immediately noticeable phenomena of democratic politics can be explained in terms of the obvious divisions which exist between different social classes, religious or ethnic groups, and political parties. These pervasive divisions influence electoral strategies, voting choices, issue-stands, governmental policies and pressure-group activities. Im portant though such decision-making processes are, it is apparent on deeper consideration that they form only one aspect of democratic politics. Of central relevance also are the toleration of one party for another, the submission of the Government to periodic elections, the existence of a broad cross-party consensus on some policies - phenom ena which all relate to the maintenance and stability of democratic procedures. It is less easy to explain stability in terms of class or party cleavage than competition, although one ingenious argument based on the effects of cross-cutting cleavages emphasises the tendency to conciliation and compromise set up in an individual who finds himself grouped with different associates on one cleavage from those with whom he is grouped on another. But cross-cutting theories do not explain why compromise rather than widespread withdrawal and alienation should result from individual cross-pressures, nor why at group level cross-cutting on cleavages of equal importance should not result in absolute intransigence and total inability to act
Keywords: Political Science